Peran Profil Pelajar Pancasila untuk Membentuk Karakter Peserta Didik Sekolah Dasar - Nurul Delima Kiska; Cindy Rizani Putri; Miranti Joydiana; Dhea Annisa Oktarizka; Sisya Maharani; Destrinelli Destrinelli (Journal on Education, 2023)
The Pancasila profile has a very important role in the formation of the character of students. The type of research used is literature riview, namely describing the role of the Pancasila profile on the character of students in elementary schools. The data collection model used is a literature study. The results found were in implementing the Pancasila Student Profile which consisted of faith, piety to God Almighty and Noble Morals, Global Diversity, Independent, Mutual Cooperation, Critical Reasoning, and Creative, which really supported the development of students when in the ever-growing field of education.